Research strategies in the social sciences : a guide to new approaches - Scarbrough, Elinor; Tanenbaum, Eric (Oxford University Press, 1998)
In this volume, a team of experts sets out various analytic tools available to social scientists from social science methodology. It guides them through the maze of advanced techniques applicable across the range of the social sciences.